Human Hepatitis B Virus Negatively Impacts the Protective Immune Crosstalk Between Natural Killer and Dendritic Cells. Issue 2 (24th May 2021) - De Pasquale, Claudia; Campana, Stefania; Barberi, Chiara; Sidoti Migliore, Giacomo; Oliveri, Daniela; Lanza, Marika; Musolino, Cristina; Raimondo, Giovanni; Ferrone, Soldano; Pollicino, Teresa; Ferlazzo, Guido
Abstract : Background and Aims: Natural killer (NK) cells play a crucial role in the clearance of human viruses but their activity is significantly impaired in patients infected with chronic hepatitis B (CHB). Cooperation with dendritic cells (DCs) is pivotal for obtaining optimal NK cell antiviral function; thus, we investigated whether HBV might impact the ability of DCs to sustain NK cell functions. Approach and Results: Human DCs were poor stimulators of interferon‐gamma (IFN‐γ) production by NK cells when exposed to HBV, while maintaining the capability to trigger NK cell cytotoxicity. HBV prevented DC maturation but did not affect their expression of human leukocyte antigen class I, thus allowing DCs to evade NK cell lysis. Tolerogenic features of DCs exposed to HBV were further supported by their increased expression of IL‐10 and the immunosuppressive enzyme indoleamine 2, 3‐dioxygenase, which contributed to the impairment of DC‐mediated NK cell IFN‐γ production and proliferation, respectively. HBV could also inhibit the expression of inducible immunoproteasome (iP) subunits on DCs. In fact, NK cells could induce iP subunit expression on DCs, but they failed in the presence of HBV. Remarkably, circulating blood DC antigen1 (BDCA1) + DCs isolated from patients with CHB were functionally compromised, hence altering, in turn, NK cell responses. Conclusions: The abnormal NK–DC interplay caused by HBV may significantly impair the efficacy of antiviral immune response in patients with CHB.